2018
DOI: 10.1113/jp275009
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative capacity varies along the length of healthy human tibialis anterior

Abstract: The rate of phosphocreatine (PCr) recovery (k ) after exercise, characterizing muscle oxidative capacity, is traditionally assessed with unlocalized P magnetic resonance spectroscopy (MRS) using a single surface coil. However, because of intramuscular variation in fibre type and oxygen supply, k may be non-uniform within muscles. We tested this along the length of the tibialis anterior (TA) muscle in 10 male volunteers. For this purpose, we employed a 3T MR system with a P/ H volume transmit coil combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 59 publications
5
50
1
Order By: Relevance
“…The significantly higher end‐exercise PCr depletion and higher postexercise perfusion found proximally are in good agreement with results of Boss et al, who used an exhaustive exercise paradigm in tibialis anterior. Although submaximal exercise was performed in our study, significant differences of end‐exercise pH and PCr recovery times were found, in contrast to . This could be explained by the fact that the fraction of oxidative Type I muscle fibers is higher in the tibialis anterior which is considered to work in a more oxidative regime compared to the GM .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The significantly higher end‐exercise PCr depletion and higher postexercise perfusion found proximally are in good agreement with results of Boss et al, who used an exhaustive exercise paradigm in tibialis anterior. Although submaximal exercise was performed in our study, significant differences of end‐exercise pH and PCr recovery times were found, in contrast to . This could be explained by the fact that the fraction of oxidative Type I muscle fibers is higher in the tibialis anterior which is considered to work in a more oxidative regime compared to the GM .…”
Section: Discussionsupporting
confidence: 90%
“…Functional and metabolic heterogeneity along a single muscle group has been found recently in a study using 31 P MRS and 1 H MRI during multiple successive exercise recovery experiments in tibialis anterior at 3 T. The simultaneous acquisition of complementary data, in combination with the the high specificity of a multi‐slice and multi‐voxel protocol and increased sensitivity of measurements at 7 T, allow for an advanced investigation of intramuscular heterogeneity in functional and metabolic exercise response along human calf muscles.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…provided new information about the spatial variability of energy metabolism within a single lower leg skeletal muscle (Boss et al . 2018). The authors investigated the oxidative capacities along the tibialis anterior (TA) muscle using a dedicated phased array probe with five coil elements allowing 31 P‐MRS measurements both during and after submaximal and exhaustive voluntary ankle dorsiflexion contractions in 10 healthy young men.…”
mentioning
confidence: 99%
“…Boss et al . (2018) assumed that the lower relative 1 H‐MRI signal in the TA distal part was at least in part related to a lower oxygen supply and/or a lower local perfusion due to a potential difference in muscle fibre‐type composition along the length of the TA. Nevertheless, the authors noted that muscle tension production and energy requirement during the submaximal voluntary contractions could have been non‐uniform along the TA.…”
mentioning
confidence: 99%